Analysis Of LST Performance (ESG Performance) In Four Mineral And Coal Mining Companies - Fajar Kurniawan; Juniati Gunawan (International Journal of Economics, Business and Innovation Research, 2024)
Indonesia is one of the world's largest coal producers and exporters. Since 2005, when it surpassed Australia's production, Indonesia has been the leading exporter of thermal coal. This study aims to analyse the performance of lst implementation (esg performance) in four mineral and coal mining companies. This study uses a qualitative approach to analyse the role of ESG implementation in mining and mineral companies as well as the issues and strategies applied. The subjects of this research are PT Antam Tbk, PT Vale Indonesia Tbk, PT Bukit Asam Tbk, PT Adaro Energy Tbk. Survey respondents were directors, senior managers, managers, officers/executives of PT Antam, Tbk, PT Vale Indonesia, Tbk, PT Bukit Asam, Tbk, PT Adaro Energy, Tbk. This research was analysed using content analysis. Primary data was obtained from interviews and questionnaires distributed to directors, senior managers, managers, officers/executives who responded. Based on the analysis of the implementation of ICMM at PT Antam, Tbk, PT Vale Indonesia, Tbk, PT Bukit Asam, Tbk, PT Adaro Energy, Tbk there are still many that are not optimal overall there are several important points that are carried out but there are several principles that are still less than optimal in the implementation of ICMM.The implementation of ICMM supported by the transparency of mineral and coal companies and visibility is able to provide an overview to shareholders of mineral and coal companies regarding the potential benefits of implementing ICMM in terms of mineral and coal company performance. High awareness of mineral and coal companies towards governance also has a positive impact on the progress of mineral and coal companies, where many parties are interested in assisting mineral and coal companies in developing new innovations for the sustainability of mineral and coal companies.The research only discusses all subjects in mineral and coal companies about ESG performance in a sustainable manner in mineral and coal companies PT Antam, Tbk, PT Vale Indonesia, Tbk, PT Bukit Asam, Tbk, PT Adaro Energy, Tbk. and the extent of ICMM implementation that has been carried out by the management of mineral and coal companies for sustainable economic growth (SDGs). And to what extent the Application of ICMM has been carried out by the management of mineral and coal companies for sustainable economic growth (SDGs).